Diagnostic pathway to amyotrophic lateral sclerosis (ALS): the significance of Babinski's sign in a unique patient and the necessity for a multidisciplinary approach. (9th January 2013) - Bulthuis, Vincent; Vlooswijk, Marielle; Santbrink, Henk van; Schijns, Olaf
Abstract : In this case report, we present a patient with rare diagnosis of amyotrophic lateral sclerosis (ALS). In this patient, four different neurological disorders were diagnosed in a short-time period of 8 months. The first three diagnoses, chronic low back and leg pain, a left frontal gemistocytic astrocytoma WHO grade 2 and suspected Lyme's disease, could not fully explain the signs of physical examination. Finally, the diagnosis of ALS could reduce these signs to the same denominator.